Self-Regulated Learning Strategy Instructions in Reading Comprehension Skill Learning During Outbreak Era - Nurjanah, Ratih Laily; Pratama, Mochamad Rizqi Adhi (Journal of English Language Teaching and Linguistics, 2020)
The online learning should be limited by principles and apply proper strategies. One of them is Self-Regulated Learning (SRL) strategy. Applying this strategy must be guided by proper instructions and procedures. In reading skill teaching and learning, this strategy is considered suitable to make students learn independently without letting them lost in the processes. This study aims to; 1) develop tasks instructions on reading comprehension skill to help students learn independently during outbreak era, 2) get students’ perspectives on how SRL works on them. The method is research and development cycle. The students’ perspectives are measured using Likert scale. The results showed that there need to be specific and clear instructions stating time, purposes of the tasks, giving students log to monitor their learning process, encouraging them to get help from lecturers or peers, and encouraging themselves to evaluate the process to find proper strategy for them.